Systematic Review: The Antihelminthic Effect of Turmeric Rhizome Extract on Ascaris Parasitic Worm - ratri mauluti larasati ratri mauluti larasati (Journal of Pharmaceutical and Natural Resources, 2025)
Worm infections remain a significant health issue globally, including in Indonesia. The primary treatment for worms is the use of deworming medication, but this can have side effects. Turmeric produces various secondary metabolites that can be developed as drugs against pathogenic infections. Therefore, a literature review is needed to examine the anthelmintic activity of turmeric against Ascaris worms. This review employed a literature review method, searching for primary data sources in the form of national and international journals from the past 10 years. The results indicate that turmeric rhizomes contain various active antihelminthic compounds that can treat Ascaris worm infections through various mechanisms, including inhibition of microtubulin proteins, muscle paralysis that inhibits motility, and disruption of worm digestion, leading to death. The active compounds in turmeric rhizomes have been shown to have a high affinity for beta-tubulin proteins, which play a key role in Ascaris worm motility.